New insights into highly potent tyrosinase inhibitors based on 3-heteroarylcoumarins: Anti-melanogenesis and antioxidant activities, and computational molecular modeling studies. Issue 5 (1st March 2017) - Pintus, Francesca; Matos, Maria J.; Vilar, Santiago; Hripcsak, George; Varela, Carla; Uriarte, Eugenio; Santana, Lourdes; Borges, Fernanda; Medda, Rosaria; Di Petrillo, Amalia; Era, Benedetta; Fais, Antonella
Graphical abstract: Abstract: Melanogenesis is a physiological pathway for the formation of melanin. Tyrosinase catalyzes the first step of this process and down-regulation of its activity is responsible for the inhibition of melanogenesis. The search for molecules capable of controlling hyperpigmentation is a trend topic in health and cosmetics. A series of heteroarylcoumarins have been synthesized and evaluated. Compounds4 and8 exhibited higher tyrosinase inhibitory activities (IC50 = 0.15 and 0.38 μM, respectively), than the reference compound, kojic acid (IC50 = 17.9 μM). Compound4 acts as competitive, while compound8 as uncompetitive inhibitor of mushroom tyrosinase. Furthermore, compounds2 and8 inhibited tyrosinase activity and melanin production in B16F10 cells. In addition, compounds2 –4 and8 proved to have an interesting antioxidant profile in both ABTS and DPPH radicals scavenging assays. Docking experiments were carried out in order to study the interactions between these heteroarylcoumarins and mushroom tyrosinase.